The Effect of Diet with Low Protein and Intermittent Lighting on Ascites Induced by Cold Temperatures and Growth Performance in Broilers - Bolukbasi, S. Canan; Emsen, Hakki (International Journal of Poultry Science, 2006)
In this study we aimed to investigate the effect of intermittent lighting and feed with low protein on ascites induced by cold temperatures and subsequent effect on growth performance of young male and female broiler chickens. A total of 300 male and 300 female broiler chickens aged one day were used for the treatment. Research was conducted as three groups intermittent lighting, low protein (18 %), and control) with four replicates. All of the groups were fed ad-libitum. (Intermittent lighting application was started on the 8 day of study. On the 21 day of the treatment, chicks in all groups were divided into two parts and moved to compartments in cold house (16oC) to induce ascites. From the live weight point of view the highest value were determined from the control and intermittent lighting groups and followed by low protein-diet group. Feed consumption was determined as highest in the control group, and lowest in the low protein-diet group. Live weight gain were determined highest in the control and intermittent light groups. The best feed conversion ratios were determined from intermittent lighting groups. Weight gain was higher in males than females. Body weight was higher in birds kept in the cold house during the study. At the end of the experiment it was determined that, no mortality was recorded due to ascites in low protein-diet group. It was concluded that low protein-diet was effective for preventing ascites in cold stress.